2022
DOI: 10.1186/s43058-021-00251-5
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to implementation of pediatric emergency department interventions for parental tobacco use and dependence: a qualitative study using the theoretical domains framework

Abstract: Background Pediatric emergency department (PED) and urgent care (UC) professionals can play a key role in delivering evidence-based guidelines to address parental tobacco use and child tobacco smoke exposure (TSE). Understanding PED/UC professionals’ perceptions regarding these guidelines is the first step in developing and implementing a TSE screening and counseling intervention in these settings. This study aimed to use the theoretical domains framework (TDF) to identify current screening and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…For example, one review on screening for harmful alcohol use in clinical settings reported clinician bias related to alcohol health literacy, knowledge of consumption guidelines, the degree of comfort in screening, and the perception of client willingness to be screened (Johnston, 2022 ). Another study on SBIRT for smoking cessation also reported deficits in knowledge inclusive of counselling methods and referrals, beliefs about capabilities and confidence to screen, and environmental context and resources like lack of time, training, and material information (Merianos et al, 2022 ). Attempts to implement SBIRT for gaming should consider each of these issues identified in the TDF prior to implementation and evaluate the degree to which they have been addressed.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one review on screening for harmful alcohol use in clinical settings reported clinician bias related to alcohol health literacy, knowledge of consumption guidelines, the degree of comfort in screening, and the perception of client willingness to be screened (Johnston, 2022 ). Another study on SBIRT for smoking cessation also reported deficits in knowledge inclusive of counselling methods and referrals, beliefs about capabilities and confidence to screen, and environmental context and resources like lack of time, training, and material information (Merianos et al, 2022 ). Attempts to implement SBIRT for gaming should consider each of these issues identified in the TDF prior to implementation and evaluate the degree to which they have been addressed.…”
Section: Discussionmentioning
confidence: 99%
“…The domains provide a theoretical lens through which one can identify all the cognitive, affective, and environmental influences on behavior. The TDF has been applied in many areas where changing physicians' behaviour is important, and has been employed, to better understand parameters that may facilitate or hinder an intervention's success (Abboud et al, 2022;Connell et al, 2014;Curran et al, 2013;Debono et al, 2017;Gondi et al, 2021;Huyer et al, 2018Huyer et al, , 2018Merianos et al, 2022;Patey et al, 2012). Despite its popularity, TDF has not yet been applied to understand physicians' challenges in implementing soft communication skills.…”
Section: Introductionmentioning
confidence: 99%